MEANS OF CLASS ACTION LAWSUIT AS AN ALTERNATIVE AND SOLUTION FOR RECOVERING STATE AND COMMUNITY FINANCIAL LOSSES IN CORRUPTION DIRECT CASH ASSISTANCE VILLAGE FUNDS - Hairuddin Tomu; Muhadar Muhadar; Musakkir Musakkir (Sekolah Pascasarjana Universitas Swadaya Gunung Jati, 2023)
The purpose of this study was to analyze the means of class action lawsuits that can be used as an alternative to recovering state losses and community losses as direct victims of Village Fund Direct Cash Assistance budget corruption. This type of research is normative legal research, namely looking at law from the point of view of norms which of course is prescriptive, using an analytical descriptive approach, namely describing the position of law as it is now. The legal materials used are primary legal materials, secondary legal materials, and tertiary legal materials obtained through library research, so that deeper analysis and understanding can be carried out so that there is a strengthening of the legal basis to produce good legal analysis. The collected legal materials were then analyzed using qualitative analysis techniques. The results of the study show that the use of class action lawsuits can be used as an alternative to recover state losses and community losses due to acts of corruption in the Village Direct Cash Assistance budget. Class action facilities are far more effective and efficient in efforts to eradicate corruption which do not burden the state budget, compared to enforcing criminal law through the criminal justice system (police, prosecutors, courts, and correctional institutions). In addition, the implementation of the execution of the return of compensation through class action facilities is more accommodative and equivalent because the legal interests of the injured stakeholder, in this case, the State and the people of the Direct Cash Assistance (Bantuan Langsung Tunai/BLT) Fund Beneficiary Group, can both be restored.